Bond markets, analysis and strategies - Fabozzi, Frank J.; Donna Battista (Pearson Education, NJ : Prentice Hall, 2010)
This is a special international edition of an established title widely used by college and universities throughout the world, providing up-to-date information about the bond market and the tools for managing bond portfolios. Pearson Education International, published this special edition for the benefit of students outside the United States and Canada.
Includes bibliographical references and index.
rpm 02/07/13
Loans
Keywords: Bonds; Investment analysis; Portfolio management; Bond market